Prove that is equivalent to sum of its factors, is equivalent to , and the sum of 's factors is equivalent to .
If you don't understand, check out the discussion explaining this and comment down in the solutions section if you now understand: A Perfect Factorial Number
Note: Think of as a perfect number (i.e. the sum of its factors excluding itself.)
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
6 = 3 + 2 + 1 = 5 + 1 = 6 - Proves that 6 is equivalent to the sum of its factors
6 = 3 ! = 3 ∗ 2 ∗ 1 = 6 ∗ 1 = 6 - Proves that 6 is equivalent to 3 !
3 + 2 + 1 = 3 !
3 + 2 + 1 = 3 ∗ 2 ∗ 1
5 + 1 = 6 ∗ 1
6 + 6 = 1 2 = 6 - Proves that the sum of 6 's factors is equivalent to 3 !
Therefore the answer is Yes.